SPONTANEOUS LEVITATION OF PLUCKED HUMAN HAIRS ON A GLASS SLIDE WHEN IMMERSED IN LIQUID POTASSIUM FERRICYANIDE. SUPPORTING A TABLETOP MICROSCOPY METHODOLOGY FOR THE IMAGING OF ELECTROMAGNETIC ENERGY IN PLANT AND ANIMAL TISSUE - Embi, Abraham A. (International Journal of Research -GRANTHAALAYAH, 2022)
“in a seminal paper describing the origin of magnetic fields in the human body Cohen et al. (1980) by using sophisticated equipment stated: “Most of the field over the head is produced by electrical sources associated with the hair follicles of the scalp; this field is produced only as a response to touching or pressing the scalp in regions where the hair is dense”. Recently, an optical microscopy method was developed in 2015 and published a year later Scherlag et al. (2016) that also detects bioelectromagetic fields from hair follicles”.